1947
DOI: 10.1021/ac60005a024
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen in Organic Compounds

Abstract: The promising micromethod of Unterzaucher for the direct determination of oxygen in organic compounds has been investigated. The procedure involves pyrolysis of the compound in a stream of nitrogen and conversion of all the oxygen in the pyrolysis products to carbon monoxide over carbon at 1120°C.The carbon monoxide is oxidized to carbon dioxide by iodine pentoxide, and the equivalent amount of iodine liberated is determined titrimetrically. A furnace meeting the high-temperature requirements is described. Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1949
1949
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The method that has won great popularity for the direct determination of oxygen is the one first developed by Sehütze ( 202) and later modified by Zimmermann (271) and Unterzaucher (235). It is the latter's modification that has been developed in this country by Aluise et al (5). The essential features of this determination consist in decomposition of the sample in a stream of nitrogen made oxygen-free by passage over heated copper and the ultimate conversion of all the oxygen of the organic compound to carbon monoxide by passing the gases over heated charcoal which must be maintained at 1100°C.…”
Section: Oxygenmentioning
confidence: 99%
“…The method that has won great popularity for the direct determination of oxygen is the one first developed by Sehütze ( 202) and later modified by Zimmermann (271) and Unterzaucher (235). It is the latter's modification that has been developed in this country by Aluise et al (5). The essential features of this determination consist in decomposition of the sample in a stream of nitrogen made oxygen-free by passage over heated copper and the ultimate conversion of all the oxygen of the organic compound to carbon monoxide by passing the gases over heated charcoal which must be maintained at 1100°C.…”
Section: Oxygenmentioning
confidence: 99%
“…This error attains greater relative significance when applied to compounds containing low amounts of oxygen. Aluise et al (2) have indeed shown that more precise and ac-if components of the residue undergo change in weigh t during ashing. The Unterzaucher method, although generally satisfactory, gives incorrect results on organic products containing inorganic carbonates or oxides.…”
mentioning
confidence: 95%
“…It is also of interest to note that Aluise and his coworkers (11) in 1947 were troubled with a variable blank in the oxygen determination which they could not explain. They attributed it to impurities in the nitrogen carrier which somehow got by the hot copper in their purifying train.…”
mentioning
confidence: 99%